Two new species of Sinacroneuria Yang & Yang, 1995 (Plecoptera: Perlidae) from Guizhou, southwestern China - Huo, Qing-Bo; Du, Yu-Zhou (Zootaxa, 2020)
Two new species of Sinacroneuria, S. huzhengkuni Du & Huo and S. lii Huo & Du from Guizhou Province of southwestern China are described including color images.